PRODUKTIVITAS KERJA DITINJAU DARI PENGEMBANGAN KARIR, MOTIVASI DAN SIKAP (STUDI PADA PT. BCA MULTIFINANCE SURAKARTA) - Tomi Irwan Trisnanto; Istiatin, Istiatin,; Eny Kustiyah (JURNAL ILMIAH EDUNOMIKA, 2020)
The research aims to find out and describe the influence of simultaneously or partial career development, motivation and attitude towards work productivity in PT. BCA Multifinance Surakarta. This methodology research using quantitative descriptive research. The population was all employees PT. BCA Multifinance Surakarta is 47 people. The number of samples was determined with the formula Arikunto and the result 47 respondents. Sampling method using sensus sampling. The questionnaire used for data retrieval. Data analysis technique used was statistic analysis is multiple linier regression, F test, t test and determination coefficient. This test results the career development, motivation and attitude simultaneously and significance effect on work productivity in PT. BCA Multifinance Surakarta. Career development influential positive and significance effect against the work productivity in PT. BCA Multifinance Surakarta. Motivation influential positive and significance effect against the work productivity in PT. BCA Multifinance Surakarta. Attitude influential positive and significance effect against the work productivity in PT. BCA Multifinance Surakarta. Keywords : Work Productivity, Career Development, Motivation, Attitude